JUMPA Vol. 4 No. 1, Feb 2017 ANALISIS KUALITAS PELAYANAN DENGAN MENGGUNAKAN METODE ANALISIS GAP PADA PT. PLN (PERSERO) RAYON BALEENDAH: ANALISIS KUALITAS PELAYANAN DENGAN MENGGUNAKAN METODE ANALISIS GAP PADA PT. PLN (PERSERO) RAYON BALEENDAH - Ulfah Novianty Santosa STIE Y.A.I (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
The number of complaints filed by customers on a state-owned companymaking state-owned companies should be able to maintain and improve service quality.No exception PT. PLN (Persero) as the state-owned company in the electricity sector. Notonly distribution office but branch offices should be able to maintain and improve thequality of services, one of which is PT. PLN (Persero) Rayon Baleendah. This study aimsto determine whether there GAP atara customer perceptions and expectations on thequality of services based on five dimensions of service quality, ie reliability,responsiveness, assurance, empathy and tangibles to the PT. PLN (Persero) RayonBaleendah.This research uses descriptive quantitative method by using samplingtechniques with this type of sampling sampling nonprobability incidental. The datacollection is done by distributing questionnaires to 100 customers of PT. PLN (Persero)Rayon Baleendah. The analysis technique used is descriptive analysis, Gap analysis andscience to map the graph of Gap analysis to serve as advice for the company. Based on theresults of this study found that the quality of services provided by PT. PLN (Persero)Rayon Baleendah give a good perception, but when compared with the expectations ofcustomers, found their GAP 5 because customer expectations are higher than on thecustomers' perception of service quality PT. PLN (Persero) Rayon Baleendah.